Antibacterial Potency of Various Concentrations of Pineapple Peel Extract (Ananas comosus) against Enterococcus faecalis - Bela Yulia Sari; Rini Bikarindrasari; Billy Sujatmiko (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2023)
Introduction: Enterococcus faecalis is a Gram-positive bacterium commonly found in cases of failed root canal treatment. Irrigation material with antibacterial effects are important in supporting the success of root canal treatment. Pineapple peel as a natural ingredient is reported to contain compounds such as flavonoids, saponins, tannins, and bromelain enzymes that have been proven antibacterial effects. Purpose: To determine antibacterial potency of pineapple peel extract (Ananas comosus) with concentrations of 1.56%, 3.125%, 6.25% and 12.5% against E. faecalis. Methods: In vitro quasi-laboratory experimental study with a post-test only control group design consisting of pineapple peel extract with concentrations of 1.56%, 3.125%, 6.25%, 12.5%, and aquadest as negative control with repetition 6 times. The inhibition test was determined using the disc diffusion method on Mueller-Hinton Agar media. The MIC value can be determined using the broth dilution method and the MBC value can be determined using the solid dilution method. The inhibition zone diameter data were analyzed using One Way ANOVA test and Post Hoc Tukey test. Results: Pineapple peel extract with concentrations 12,5% had the largest mean inhibition zone, which is was 3.13 mm. The MIC and MBC values of pineapple peel extract were determined at a concentration of 6.25%. Conclusion: Pineapple peel extract (Ananas comosus) has antibacterial potency against Enterococcus faecalis.